2021
DOI: 10.3390/en14206756
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Transient Pipe Flow in Plastic Pipes with Modified Discrete Bubble Cavitation Model

Abstract: Most of today’s water supply systems are based on plastic pipes. They are characterized by the retarded strain (RS) that takes place in the walls of these pipes. The occurrence of RS increases energy losses and leads to a different form of the basic equations describing the transient pipe flow. In this paper, the RS is calculated with the use of convolution integral of the local derivative of pressure and creep function that describes the viscoelastic behavior of the pipe-wall material. The main equations of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Failure of hydraulic pipelines is a critical problem in aviation industry. Factors what is associated with pipelines failure can be divided on a groups by: material characteristics problem (Τawancy & Al-Hadhrami, 2009;Lubecki et al, 2021); pipelines geometry problem (Firoozabad et al, 2016); during an environmental conditions (Fedorko et al, 2015;Karpenko et al, 2022); by internal or external loadings (Edjeou et al, 2018;Luczko & Czerwinski, 2014); residual stresses for a metal and plastic pipelines (Mankari & Acharyya, 2018;Urbanowicz et al, 2021) and in final by manufacturing flaws (Drumond et al, 2016). The interaction of these factors is very complex to analyse.…”
Section: An Aircraft Pipelines Failure and Maintenance Problemsmentioning
confidence: 99%
“…Failure of hydraulic pipelines is a critical problem in aviation industry. Factors what is associated with pipelines failure can be divided on a groups by: material characteristics problem (Τawancy & Al-Hadhrami, 2009;Lubecki et al, 2021); pipelines geometry problem (Firoozabad et al, 2016); during an environmental conditions (Fedorko et al, 2015;Karpenko et al, 2022); by internal or external loadings (Edjeou et al, 2018;Luczko & Czerwinski, 2014); residual stresses for a metal and plastic pipelines (Mankari & Acharyya, 2018;Urbanowicz et al, 2021) and in final by manufacturing flaws (Drumond et al, 2016). The interaction of these factors is very complex to analyse.…”
Section: An Aircraft Pipelines Failure and Maintenance Problemsmentioning
confidence: 99%
“…It is well known that cavitation is a dangerous process that affects pipelines and flow machines [38]. Urbanowicz et al [39] conducted research on modeling transient pipe flow in plastic pipes with a modified discrete bubble cavitation model. In the physical model of unsteady pipe flow, they assumed the importance of three phenomena: unsteady wall shear stress, vaporous cavitation, and pipe wall retarded strain.…”
Section: Review Of Contribution To the Special Issuementioning
confidence: 99%
“…The authors noted that the comparison of computed results with measurements showed that the novel discrete bubble cavity model predicts pressure and velocity waveforms, including cavitation and retarded strain effects, with sufficient precision. The authors noticed that the influence of unsteady friction on the damping of pressure waves was much smaller than the influence of retarded strain [39].…”
Section: Review Of Contribution To the Special Issuementioning
confidence: 99%
“…Several other features have been explored in the past decade, such as the presence of in-line valves or sudden cross-section changes [16][17] and pipe networks [18][19] . Soares et al [20] , Urbanowicz et al [21] , and Mousavifard [22] also studied the effects of cavitating flows in viscoelastic pipes. Meanwhile, other works were concerned with identifying pipe faults/anomalies in viscoelastic pipelines, as broadly presented by Che et al [23] .…”
Section: Introductionmentioning
confidence: 99%